A possible missing (or theorized) link between absurdities in the human psyche and in the Theatre of the Absurd, using fairy tales as a connecting vehicle - Dell, Bianca (Stellenbosch : Stellenbosch University, 2022)
Thesis (MDram)--Stellenbosch University, 2022.